Karakterisasi Senyawa Metabolit Buah Duku (Lansium domesticum) Berdasarkan Studi Literatur serta Potensi Bioaktifnya dalam Bidang Kesehatan - Evelyn Luna Anggraini; Ardi Mustakim (MUARA KESEHATAN : Jurnal Ilmiah Ilmu Kesehatan, 2026)
Duku fruit (Lansium domesticum) is a tropical fruit that has potential as a natural source of metabolite compounds with various bioactive properties beneficial to human health. This study aimed to characterize the metabolite compounds present in duku fruit based on a literature review and to examine their bioactive potential in the health field. The research method employed was a literature study by reviewing relevant national and international scientific articles, particularly studies reporting the types of metabolite compounds, analytical methods used, and bioactive activities of duku fruit. The literature review results indicate that duku fruit contains various secondary metabolites, including flavonoids, phenolic compounds, terpenoids, alkaloids, and saponins, which have been identified using analytical methods such as phytochemical screening, chromatography, and spectroscopic techniques. These compounds have been reported to exhibit bioactive activities, including antioxidant, antibacterial, anti-inflammatory, and antidiabetic potentials. Based on the comparative analysis of the literature, duku fruit shows promising potential to be developed as a natural source for health-related applications. This review is expected to provide a scientific reference for further research on the utilization of duku fruit in the health sector